Sex-specific Associations Between Type 2 Diabetes Incidence and Exposure to Dioxin and Dioxin-like Pollutants: A Meta-analysis - Gang, Noa; Van Allen, Kyle; Villeneuve, Paul J.; MacDonald, Heather; Bruin, Jennifer E. (Frontiers in Toxicology, 2022)
The potential for persistent organic pollutants (POPs), including dioxins and dioxin-like polychlorinated biphenyls (DL-PCBs), to increase the risk of incident diabetes in adults has been extensively studied. However, substantial variability exists in the reported associations both between and within studies. Emerging data from rodent studies suggest that dioxin disrupts glucose homeostasis in a sex-specific manner. Thus, we performed a review and meta-analysis of relevant epidemiological studies to investigate whether there are sex differences in associations between dioxin or DL-PCB exposure and type 2 diabetes incidence. Articles that met our search criteria (n=81) were organized into the following subcategories: data stratified by sex (n=13), unstratified data (n=45), and data from only one sex (n=13 male, n=10 female). We also considered whether exposure occurred either abruptly at high concentrations through a contamination event (“disaster exposure”) or chronically at background concentrations (“non-disaster exposure”). There were 8 studies that compared associations between dioxin/DL-PCB exposure and diabetes risk in males versus females within the same population. When all sex-stratified or single-sex studies were considered in the meta-analysis, the summary relative risk (RR) for incident diabetes among those exposed relative to reference populations was 1.78 (95% CI = 1.37-2.31) and 1.95 (95% CI = 1.56-2.43) for female and males, respectively. However, when we restricted to disaster-exposed populations, the RR was higher in females than males (2.86 versus 1.59, respectively). In contrast, in non-disaster exposure populations and the RR for females was lower than males (1.40 and 2.02, respectively). Our meta-analysis suggests there are sex differences in the associations between dioxin or DL-PCBs and incident diabetes, and that the mode of exposure modifies these sex differences.